KAJIAN INTERTEKSTUAL DALAM NOVEL AYAT-AYAT CINTA KARYA HABIBURRAHMAN EL SHIRAZY DENGAN NOVEL DZIKIR-DZIKIR CINTA KARYA ANAM KHOIRUL ANAM - Roma Nur Asnita (Fakultas Adab dan Humaniora UIN Raden Fatah, 2013)
Abstract: Indonesian literature can be found in the intertextual relationship between literary works such as the novel Ayat- Ayat Cinta with Dzikir-dzikir cinta. Issues discussed in this article is how the intertextual relationship between the novel Ayat- Ayat Cinta with Dzikir-dzikir cinta . The scope of the issues discussed are two novels that intertextual relations in terms of theme , plot , character and characterization , perspective , and background . Also, to describe the intertextual relationship novel Ayat - Ayat Cinta with Dzikir-dzikir cinta in terms of theme , plot , character and characterization , perspective , and background . Based on the results of the discussion , intertextual relationship between the novel Ayat- Ayat Cinta with novel Dzikir-dzikir cinta are similarities in terms of theme , plot , and point of view . In addition , there is a contradiction and transformation between the two novels is that in terms of character and characterization as well as the background . Similarities between the two novels is that both religious -themed novel , contains teachings about human life to be able to behave and act in accordance with the true teachings of Islam . Keywords : intertextual study , intertextual relationships .